A study of the relationship between the symbolic adoption of Human Resource Information Systems', technology adoption factors, and work-related outcomes - Sonalee Srivastava; Badri Bajaj (International Journal of Business Science & Applied Management (IJBSAM), 2022)
Over recent years, the Human Resource Information System (HRIS) has gained tremendous impetus in industry. Still, the literature states that most information system failures result from employee resistance and subsequent opposition behaviour. To address the gap in the literature, this study has targeted employees' technological symbolic adoption to analyze employee resistance behaviour. As employees' technological symbolic adoption occurs much before their actual technology adoption. Symbolic adoption means users' mental evaluation of the technology used for their work. This study has taken the perspective of HRIS symbolic adoption and identifies its antecedents and outcome factors, i.e., technology adoption factors and work-related outcomes. Thus, this study investigates the relationship between technology adoption factors (performance expectancy, effort expectancy, social influence, and information quality) and work-related outcomes (work-life balance, engagement, and creativity). Furthermore, this study examines the mediating effect of HRIS symbolic adoption between the above-stated factors. 415 HRIS end-users from the HR department of small-to-medium-sized organizations were recruited to collect data. This paper offers a theoretical and practical contribution, extending the line of research on the end user's symbolic adoption domain, and helping small and medium-size organizations to better understand end-users' technological adoption factors. In light of this study's findings, HR practitioners and management should focus on effective HRIS interventions in small and medium-sized organizations to stay ahead with engaged, creative, and balanced employees.
Keywords: 650; human resource information system; symbolic adoption; work-life balance; engagement; creativity